Aberrations of mourning - Rickels, Laurence A. (University of Minnesota Press, 2011)
"Aberrations of Mourning," originally published in 1988, is the long unavailable first book in Laurence A. Rickels's "unmourning" trilogy, followed by "The Case of California" and "Nazi Psychoanalysis.". Rickels studies mourning and melancholia within and around psychoanalysis, analyzing the writings of such thinkers as Freud, Nietzsche, Lessing, Heinse, Artaud, Keller, Stifter, Kafka, and Kraus. Rickels maintains that we must shift the way we read literature, philosophy, and psychoanalysis to go beyond traditional Oedipal structures. "Aberrations o.